The Role of Women in Terrorism in Indonesia - Mahardhika, Dyah Ayu; Priyanto, Sapto (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2023)
The involvement of women in terrorism in Indonesia has been seen since 2000 which was marked by Munfiatun's involvement as Noordin Muhammad Top's second wife in acts of terrorism at the Marriot Hotel in 2003 and the Australian Embassy in Jakarta in 2004. At this time, women do not act as the main actors but as supporters based on the relationship between husband and wife. Changes in the status of women's roles in acts of terrorism began to be seen in 2016 after the arrest of Dian Yulia Novi as the perpetrator in the pot bomb case in Bekasi. After the arrest, there was an increase in the involvement of women in acts of terrorism. Social media has succeeded in changing the role of women into perpetrators of terrorist actions. This article aims to determine the factors causing the increase in the role of women in terrorism in Indonesia, both in the form of bomb threats, attacks on officers, and suicide bombings. This study uses qualitative methods with secondary data sourced from court decisions and news in the national media from 2016 to 2022. This research found that husband and wife relationships aren't the main cause of women's involvement in Indonesian terrorism. Through the theory of the Hypodermic Needle, it was obtained that the media can provide information that affects society at large. These theories are considered appropriate in describing the propaganda of terrorist groups against female terror perpetrators in Indonesia where the media has a major influence in changing the thinking of the audience, directing the behavior of the audience, shaping attitudes, and even initiating the implementation of terror acts.